Developing a model of perceived value, quality of life, place attachment and destination loyalty/ Muhamad Nasyat Muhamad Nasir ... [et al.] - Muhamad Nasir, Muhamad Nasyat; Abdul Rahim, Marlisa; Hassan, Suchi; Muhamad, Siti Fariha (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Kelantan is located in the East Coast of Malaysia. This state is rich in culture and delicious local dishes. Therefore, it has bright potential to become a tourism hub in this country. However, statistics demonstrated that Kelantan received a small number of domestic tourist arrivals and receipts compared to other states. Hence, to resolve this issue, it is crucial to improve destination loyalty among local tourists. This study intends to propose a new research model which will be tested among domestic tourists visiting Kelantan. Several constructs will be assembled, such as perceived value, place attachment, quality of life and destination loyalty. The research predicts to examine five direct effects. Most importantly, two parallel mediators will be proposed in this model. The study's findings are expected to facilitate tourism management in Kelantan to boost domestic tourism within that state.